Follow-up of children who received complex invasive therapies early in life - Sauve, Reg (Pulsus Group Inc, 2006)
The present article reviews existing literature and outcome assessment processes used in programs that provide various complex paediatric therapies. The published literature is summarized, and enrolment and assessment details used in the Complex Paediatric Therapies Registry in the province of Alberta are discussed. Several studies have reported the outcomes of infants and children who received various complex invasive therapies. Four hundred eighty-three infants and children who received specific complex therapies in Alberta and survived to discharge were enrolled in neonatal follow-up programs in their home provinces. Compliance rates are 96% or higher at baseline, 18 months and four years of age. In general, cerebral palsy, blindness and deafness are very rare, but developmental delay and borderline cognitive function are more frequent. Analysis of the predictors of the adverse outcomes of such infants has permitted optimal parent counselling and initiation of efforts to improve outcomes.